Viral–Host Interactome Analysis Reveals Chicken STAU2 Interacts With Non-structural Protein 1 and Promotes the Replication of H5N1 Avian Influenza Virus - Wang, Qiao; Zhang, Qi; Zheng, Maiqing; Wen, Jie; Li, Qinghe; Zhao, Guiping (Frontiers in Immunology, 2021)
As a highly pathogenic influenza virus, H5N1 avian influenza virus (AIV) poses a great threat to poultry production and public health. H5N1 AIV has a small genome and therefore relies heavily on host cellular machinery to replicate. To develop a comprehensive understanding of how H5N1 AIV rewires host cellular machinery during the course of infection, it is crucial to identify which host proteins and complexes come into physical contact with viral proteins. Here we report the use of affinity tagging and purification mass spectrometry (AP-MS) to determine systematically the physical interactions of 11 H5N1 AIV proteins with host proteins in chicken DF1 cells. We identified with high confidence 1 043 H5N1 AIV-chicken interactions involving 621 individual chicken proteins, and uncovered a number of host proteins and complexes 2 targeted by viral proteins, including the finding that chicken Staufen double-stranded RNA binding protein 2 interacts with AIV non-structural protein 1 (NS1) and promotes replication of the virus by enhancing the nuclear export of NS1 mRNA. This dataset facilitates a more comprehensive and detailed understanding of how host machinery is manipulated during the course of H5N1 AIV infection.